Brexit and Human Rights: An opportunity? - Michelle Coleman (The Future of Human Rights in the UK, 2017)
As the United Kingdom leaves the European Union, the rights of individuals, including human rights, will be affected. While the degree of the United Kingdom’s disentanglement from the European Union depends on future negotiations, individual rights as provided through the European Union are at risk. It is widely believed that human rights will be constricted when the United Kingdom leaves the European Union. This however, need not be the case. There are many laws that will require rewriting after Brexit in order to remove Europe’s influence. This will require Parliament to undertake a major reworking of laws throughout the entire legal system. While Parliament is engaged in this work, they could choose to prioritise human rights. Taking this kind of policy on board, they could also improve domestic laws that have become severely constrained despite Europe’s influence.One such right is the right to remain silent. The right to silence in England and Wales no longer exists in practice. Although technically limited, adverse inferences can apply whenever the defendant remains silent or attempts to later change their narrative and even when the defendant remains silent on advice of counsel. Thus, an adverse inference, contributing to conviction, could be drawn in almost every case. The result is that a defendant has no real choice as either choosing to speak or exercising the right to remain silent contributes to their conviction.This paper argues that Brexit will cause legal upheaval as Parliament rewrites or reconsiders a large number of laws within the British legal system. As a result, Parliament will need to choose their priorities during the rewriting process. Parliament could use Brexit as an opportunity to prioritise human rights and set the United Kingdom out as a world leader in human rights law and policy.